Stimulatory and inhibitory regulation of calcium-activated potassium channels by guanine nucleotide-binding proteins. - Kume, H (1992)
The regulation of membrane ion channels by guanine nucleotide-binding proteins (G proteins) has been described in numerous tissues. This regulation has been shown to involve the membrane-delimited stimulatory action of G proteins on ion channels. We now show that single calcium-activated potassium channels (KCa channels) in airway smooth muscle cells are both stimulated and inhibited by G proteins in membrane patches. We demonstrate that the beta-adrenergic agonist isoproterenol stimulates channel activity via the alpha subunit of the stimulatory G protein of adenylyl cyclase, Gs, and that channel opening is inhibited by the action of the muscarinic agonist methacholine, acting via a pertussis toxin-sensitive G protein. Isoproterenol stimulated and methacholine inhibited channel activity in the same outside-out patches when GTP was present at the cytosolic surface of the patch. In inside-out patches, addition of GTP and guanosine 5'-[gamma-thio]triphosphate (GTP[gamma S]) augmented channel activity when isoproterenol was included in the patch pipette, and inhibited channel activity when methacholine was included in the pipette. Consistent with these results, in the presence of GTP[gamma S], the alpha subunit of Gs (alpha s.GTP[gamma S] complex) opened KCa channels in a dose-dependent manner, whereas in the presence of guanosine 5'-[beta-thio]diphosphate, alpha s had no effect. By contrast, application of activated alpha i or alpha o proteins did not inhibit channel activity in inside-out patches, indicating that channel inhibition is more complex than a simple alpha subunit/channel interaction, similar to the complex inhibitory regulation of adenylyl cyclase. These results suggest that hormonal regulation of KCa channels shares substantial features with the regulation of adenylyl cyclase and demonstrate that a single ion channel may serve as the regulatory target for the membrane-delimited action of stimulatory and inhibitory G proteins. Moreover, they demonstrate a potentially important functional pathway by which beta-adrenergic and other Gs-linked receptors stimulate relaxation of smooth muscle, independent of cAMP-dependent protein phosphorylation.